Recent Differentiation of Aquatic Bacterial Communities in a Hydrological System in the Cuatro Ciénegas Basin, After a Natural Perturbation - García-Ulloa, Manuel; Souza, Valeria; Esquivel-Hernández, Diego A.; Sánchez-Pérez, Jazmín; Espinosa-Asuar, Laura; Viladomat, Mariette; Marroquín-Rodríguez, Montserrat; Navarro-Miranda, Marisol; Ruiz-Padilla, Jair; Monroy-Guzmán, Camila; Madrigal-Trejo, David; Rosas-Barrera, Manuel; et al. (Frontiers in Microbiology, 2022)
Pozas Rojas is a hydrological system comprising nine isolated shallow ponds and a deep lagoon, which were temporally merged in 2010 by increased rainfall due to a tropical cyclone. In this work, we assess which components, biotic interactions or environment filtering, drive the assembly of microbial communities after a natural perturbation. Arsenic, pH and temperature are among the most significant environmental variables between each pond, clustering the samples in two main groups, whereas microbial composition is diverse and unique to each site, with no core at the OTU level and only 150 core genera when studied at the genus level. Los Hundidos lagoon has the most differentiated community, which is highly similar to the epipelagic Mediterranean Sea communities. On the other hand, the shallow ponds at the Pozas Rojas system resemble more to epicontinental hydrological systems, such as some cold rivers of the world and the phreatic mantle from Iowa. Overall, interspecific interactions, rather than environmental selection, seem to play a more important role in Pozas Rojas, bolstered by founder effects on each poza and subsequent isolation of each water body.